Pricing writer-extendable call options with Monte Carlo simulation - Wan Omar, Hazimah; Ibrahim, Siti Nur Iqmal (Penerbit Universiti Malaysia Perlis, 2024)
Writer-extendable option is an exotic option that can either be exercised at its initial maturity time or be extended to a future maturity time. Within the Black-Scholes environment, this study aims to price writer-extendable call options using the Monte Carlo simulation technique and compare the obtained prices with the closed-form pricing formula. Numerical examples are provided using the closed-form solutions and the Monte Carlo simulation via Euler scheme, which shows that the prices obtained via the latter are accurate.